The promoter effect of Nb species on the catalytic performance of Ir-based catalysts for VOCs total oxidation. Issue 5 (October 2022) - Chávez-Sifontes, Marvin; García, Adrián; Sanchis, Rut; Furgeaud, Clarisse; Mayoral, Alvaro; Arenal, Raul; Morgan, David J.; Taylor, Stuart H.; López, Jose Manuel; García, Tomás; Solsona, Benjamín
Abstract: Ir/TiO2 catalysts promoted by niobium have been synthesized, characterized by different complementary techniques, and tested for the total oxidation of a set of alkanes and their mixtures. The addition of appropriate amounts of niobium to Ir/TiO2 catalysts resulted in a remarkable increase in the catalytic activity compared to the Nb-free Ir/TiO2 catalysts. The promotion caused by the presence of niobium has been related to the massive presence of isolated IrOx surface species which, interestingly, present remarkable reducibility and, consequently, excellent catalytic activity. Conversely, the IrOx species formed in the catalyst in the absence of niobium also include IrO2 clusters with lower intrinsic reactivity. Similarly, Nb-loadings exceeding the theoretical monolayer tends to the formation of bulk Nb2 O5 species on the titania surface that provokes the formation of IrO2 nanoclusters. A positive influence on the reactivity of non-stoichiometric surface Ti 3+ species that generates oxygen vacancies is also observed. Graphical Abstract: ga1 Highlights: Nb promotes the catalytic performance of Ir/TiO2 for VOCs total oxidation. Highly dispersed IrOx isolated species are mostly obtained at optima conditions. The addition of Nb greatly improves the reducibility of IrOx species. Non-stoichiometric surface Nb +4 and Ti 3+ remarkably increases oxygen vacancies. Lower support acidity after Nb loading significantly enhances water tolerance.